2017
DOI: 10.5194/nhess-17-1725-2017
|View full text |Cite
|
Sign up to set email alerts
|

A procedure to select ground-motion time histories for deterministic seismic hazard analysis from the Next Generation Attenuation (NGA) database

Abstract: Abstract. In performance-based seismic design, groundmotion time histories are needed for analyzing dynamic responses of nonlinear structural systems. However, the number of ground-motion data at design level is often limited. In order to analyze seismic performance of structures, ground-motion time histories need to be either selected from recorded strong-motion database or numerically simulated using stochastic approaches. In this paper, a detailed procedure to select proper acceleration time histories from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
(39 reference statements)
0
2
0
3
Order By: Relevance
“…The use of non-local ground motions for seismic hazard analysis has been reported in the literature. For example, Huang et al, 2017 developed a procedure for selecting ground-motion time histories for seismic hazard analysis for several cities in Taiwan using the NGA database. Based on the selection of earthquakes, they concluded that records from local earthquakes do not necessarily match the target spectra from the hazard analyses, and a more suitable match could be achieved by using non-local ground motions.…”
Section: Database Definitionmentioning
confidence: 99%
“…The use of non-local ground motions for seismic hazard analysis has been reported in the literature. For example, Huang et al, 2017 developed a procedure for selecting ground-motion time histories for seismic hazard analysis for several cities in Taiwan using the NGA database. Based on the selection of earthquakes, they concluded that records from local earthquakes do not necessarily match the target spectra from the hazard analyses, and a more suitable match could be achieved by using non-local ground motions.…”
Section: Database Definitionmentioning
confidence: 99%
“…En atención a lo indicado, en el presente estudio se aplicará el método de escalado de registros sísmicos reales que representen la sismicidad de la región investigada. Por ejemplo, este criterio se siguió para la selección de registros apropiados para la realización de estudios sísmicos en diversas ciudades de Taiwán (Huang et al, 2017).…”
Section: Metodologíaunclassified
“…Siguiendo a Huang et al (2017), hay diversos algoritmos de selección de movimientos del terreno disponibles en la literatura (Baker, 2010;Jayaram et al, 2011;Wang, 2011). Una de las herramientas propuestas más versátiles lo constituye la aplicación web de la base de datos de movimientos del terreno del PEER (Pacific Earthquake Engineering Research Center's) -Next Generation Attenuation (NGA).…”
Section: Características De Las Fuentes Sismogénicas Principales En L...unclassified
See 1 more Smart Citation
“…It has hourly data set and has been converted into a daily data set by averaging hourly data per day. We concentrate 6 major pollutants such as Nitrogen dioxide (NO 2 ), Ozone (O 3 ), Carbon monoxide (CO), Sulfur dioxide (SO 2 ), PM 2.5 < 2.5 micrometers in diameter, PM 10 For the quality check, the air quality monitoring data were processed to facilitate the city-based cross-correlation analysis [11]. First, for each city the concentration of the daily pollutant was calculated by averaging the hourly data from all stations within that city.…”
Section: B Dataset Descriptionmentioning
confidence: 99%